Roughness comparison specimens Part 1. Specification for turned, ground, bored, milled, shaped and planes specimens (BSI, 1987)
Roughness (surface), Surface texture, Surface properties, Surface-roughness measurement, Control samples, Turning, Grinding, Boring, Milling (engineering), Planing, Material-removal processes, Sampling methods, Calibration, Tolerances (measurement), Test specimens, Marking, Comparative tests, Visual inspection (testing), Grades (quality), Samples, Length